The edge of seventeen [videorecording (DVD)] - Fremon, Kelly; Steinfeld, Hailee; Harrelson, Woody; Sedgwick, Kyra; Jenner, Blake, 1992- (Universal Pictures Home Entertainment, 2017)
High school life gets even more unbearable for Nadine when her best friend, Krista, starts dating her older brother.